Os gêneros de discurso, cenografia e ethos em discursos da obra O templo e a forca de Luiz Guilherme Santos Neves - Menezes, Rita de Cássia dos Santos (2013)
This research aims to show how the religious discourse of the preach genre, in the voice of the enunciator Brother Gregório José Maria de Bene, can influence the convincing strategy for the adherence of the slaves from the region of Serra, in the province of Espírito Santo, Brazil, to the construction of the Queimado church. The preach cited is the fundamental exert from the literary discourse O Templo e a Forca (1999), recreated by Luiz Guilherme Santos Neves, analyzed after a comprehensive scene that legitimates it as such. This work is situated in French-line Discourse Analysis’ (DA’s) studies, having Dominique Maingueneau as its main theoretical reference, which is to orient us about the scenographies provided by the priest, his image of enunciator, the conditions of the preach production, highlighting the interacting elements in the confrontation to aim at the epoch’s social conditions and at the cultural issues of the involved in the unchaining of the revolt. The main purpose was to assess the enunciation scenes and how the religious ethos is constructed in each scene with its several functions. It is common-sense to say that the religious element reconstructs itself every moment since the commitment with the communication situations. For a better understanding, we might say that those various reconstructions represent, amidst the discourses, different religious scenes, with their adherence strategies: one, that speaks in the name of God, praising the peacefulness of the country life under the shadow of the giant andirobeiras, where one can feel the silence that invites to contemplation and prayer; another one, is committed to its own selfish purposes. It speaks not to be understood, and what counts is to raise the Saint Joseph’s house, without sparing flesh and blood from the deaths to come. It is worth stressing that a naïve look is always possible over a religious text, which, according to Maingueneau (2010), is only readable associated to a vast intertext, which in turn contributes to structure the discourse. In order to enrich even more this study, we use not only the preach genre, but other approaches structuring Neves’ discourse and indicating the many-fold scenographies and their constitution as genres: Inner dialogue – solitary moments of the Brother – the Brother’s vision, and Monologue; Shared Dialogue – segmented dialogues between the enunciator and his several co-enunciators, who structure the facts reported in the discourse; and the genre exhortation addressed from the priest to the slaves. All those parts transmit moments of great conflicts recreated by the author, in a light discourse taking its reader enjoyably along its diversified images. Remember that the reader is led to believe it was all about the comic genre. And perhaps it would have been, if only it did not end up in revolt.